2020
DOI: 10.5223/pghn.2020.23.4.356
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clinical, Laboratory and Fluid Therapy Variables on Hospital Length of Stay for Children with Acute Pancreatitis

Abstract: Purpose: There have been many efforts to develop generalizable severity markers in children with acute pancreatitis (AP). Expert opinion panels have developed consensus guidelines on management but it is unclear if these are sufficient or valid. Our study aims to assess the effect of clinical and laboratory variables, in addition to treatment modality on hospital length of stay (LOS) as a proxy variable for severity in pediatric patients admitted with AP. Methods: We conducted a retrospective chart review of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Long hospital stay is associated with high hospital occupancy, increased costs, and adverse patient outcomes, such as persistent organ failure [10][11][12] . The previous studies showed that low MCH level is one of the earliest and sensitive indicators of iron de ciency in different populations [13][14][15] , suggesting that MCH positively correlated with iron level.…”
Section: Discussionmentioning
confidence: 99%
“…Long hospital stay is associated with high hospital occupancy, increased costs, and adverse patient outcomes, such as persistent organ failure [10][11][12] . The previous studies showed that low MCH level is one of the earliest and sensitive indicators of iron de ciency in different populations [13][14][15] , suggesting that MCH positively correlated with iron level.…”
Section: Discussionmentioning
confidence: 99%
“…Fluid intake above recommended maintenance did not reduce length of stay. 4 The article highlights the common etiologies of acute pancreatitis and Table 1 provides a comprehensive list. Pancreatitis may also be part of COVID-19.…”
mentioning
confidence: 99%